Vortex Lattice Instabilities in YBa(2)Cu(3)O(7-x) Nanowires - Rouco, Víctor (Materials (Basel), 2018)
High-resolution focused ion beam lithography has been used to fabricate YBa(2)Cu(3)O(7-x) (YBCO) wires with nanometric lateral dimensions. In the present work, we investigate Flux-flow instabilities in nanowires of different widths, showing sudden voltage switching jumps from the superconducting to the normal state. We present an extensive study on the temperature and field dependence of the switching characteristics which reveal that voltage jumps become less abrupt as the temperature increases, and disappear at the vortex-liquid state. On the contrary, the current distribution at the critical point becomes narrower at high temperatures. Sharp voltage switchings very close to the critical current density can be obtained by reducing the width of the nanowires, making them very appealing for practical applications.